THE MIDDLE CLASS AND POLITICAL TRANSFORMATION IN NIGERIA: AN APPRAISAL OF THE ROLE OF ASUU AND NBA - Waziri B. Adisa (European Scientific Journal, ESJ, 2014)
Since the end of the Cold War in 1989 and the collapse of one-party regimes in the Third World, many African countries have come to the conclusion that, political transformation is an inevitable process of attaining economic and political development. This process is expected to engender economic growth, improve citizens’ access to national politics and create conducive environment for wealth creation. Using cross-sectional survey and key informant interview methods, this study found that, the middle class is one of the strong agents of political change and development in contemporary Nigeria. It however, found weak involvement and participation of the Academic Staff Union of Universities and the Nigerian Bar Association in matters relating to party formation, economic growth and development, international politics and international relations contribute to limited progress made by Nigeria on the democratization process. The study found that, despite some progress made by the Academic Staff Union of Nigerian Universities (ASUU) and the Nigerian Bar Association in the democratization process, the middle class still remains one of the most marginalized classes in contemporary Nigeria.